Statistical Analysis and EEG Signal Filtering Using Design of Window Function Based on Optimization Methods - Serbet, Fatmanur; Kaya, Turgay (World Scientific Publ Co Pte Ltd, 2023)
The window functions, which are widely used in Finite Impulse Response (FIR) digital filter design with the Fourier Series Methods, aim to eliminate the oscillations adversely affecting the filter performance that occur during the filter design. Window functions, which were developed with different methods in the literature, were designed with three different optimization techniques in this study. By using Particle Swarm Optimization (PSO), Grey Wolf Colony Optimization (GWCO), Cuckoo Search Optimization (CSO) algorithms, which are among current metaheuristic optimization methods, new window functions are designed for FIR digital filter design such that the designed new window functions have different window coefficients and design parameters. The difference of the designed window functions was analyzed with the Friedman and Wilcoxon tests, which are statistical data analysis methods, and the originality of the designed window functions was proven. FIR digital filters that can perform the same operation as the designed window functions have been produced and the results obtained by performing the filtering application of the EEG signal with the produced filters are presented in the study.
Keywords: Window functions; Particle Swarm Optimization (PSO); Gray Wolf Colony Optimization (GWCO); Cuckoo Search Optimization (CSO); Friedman test; Wilcoxon test